2020
DOI: 10.3390/agriculture10060229
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Weed Infestation, Grain Health, and Productivity Parameters of Two Spelt Wheat Cultivars Depending on Crop Protection Intensification and Seeding Densities

Abstract: Spelt wheat is one of the oldest wheat with very high nutritional value. It does not have particular climatic requirements and tolerates adverse environmental conditions well. The versatile advantages of spelt wheat make it attractive to farmers, plant breeders, food technologists, and consumers. The aim of this study was to determine the effect of different crop protection systems and seeding densities on yield, weed infestation, and grain health of the spelt wheat cultivars “Rokosz” and “Schwabenspelz”. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Consistent with our study, Buczek, et al 78 reported that the gluten index in no-tillage treatment was considerably lower compared to conventional tillage and reduced tillage. Additionally, Haliniarz, et al 98 found that CT outperformed no-tillage in terms of grain density and uniformity, resulting in a significantly lower gluten index. A low gluten index suggests the weakness of gluten for the baking industry 99 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our study, Buczek, et al 78 reported that the gluten index in no-tillage treatment was considerably lower compared to conventional tillage and reduced tillage. Additionally, Haliniarz, et al 98 found that CT outperformed no-tillage in terms of grain density and uniformity, resulting in a significantly lower gluten index. A low gluten index suggests the weakness of gluten for the baking industry 99 .…”
Section: Discussionmentioning
confidence: 99%
“…All individual weed species were taken from two randomly selected places, (0.7 × 1.0 m quadrat frame), divided into species, and weighed. Next, they were averaged and expressed on a 1 m -2 basis (Haliniarz et al 2020). Each year, the weed flora of experimental fields mainly consisted of Chenopodium album L. (CHEAL), and Brassica napus (BRSNN) at densities of 513-850 g • m -2 and 547-846 g • m -2 , respectively.…”
Section: Determination Of Sorgoleone Contentmentioning
confidence: 99%
“…Haliniarz et al [10] showed that the effectiveness of the use of plant protection products in the cultivation of spelt wheat depended on the cultivar. Under intensive cultivation, lower weed infestation and higher yields were obtained for the cultivar Rokosz compared to Schwabenspelz.…”
Section: Biodiversity Of Weeds In Annual Cropsmentioning
confidence: 99%
“…Several articles have shown that crop species and habitat conditions significantly affect the abundance and botanical composition of the associated flora (segetal weeds) [4,5,9]. Moreover, it was found that the effectiveness of the use of plant protection products in wheat cultivation depended on the cultivar [10]. Increasing the intensity of the production also affects the yields of lupine [8] and spelt wheat [10], as well as the health of soybean [6] and chamomile [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation